2005
DOI: 10.2807/esw.10.26.02740-en
|View full text |Cite
|
Sign up to set email alerts
|

Tickborne encephalitis epidemiology in Estonia, 1950-2004

Abstract: The first case of tickborne encephalitis (TBE) in Estonia was reported in 1950 in the south of the country. Since that time, TBE has spread and today it is endemic in Estonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The observed branching order suggests that a change has occurred in the transmission mode within the I. ricinus ('sheep tick') group: the current representatives of the more ancestral virus lineages have their main transmission cycle between ticks and sheep/goats or grouse, while current TBEV-Eur strains cycle primarily between ticks and small mammals. Notably, TBEV is transmitted readily to man also via unpasteurized goat milk and cheese (Kerbo et al, 2005;Holzmann et al, 2009) in addition to tick bites.…”
Section: Rate Of Evolutionmentioning
confidence: 99%
“…The observed branching order suggests that a change has occurred in the transmission mode within the I. ricinus ('sheep tick') group: the current representatives of the more ancestral virus lineages have their main transmission cycle between ticks and sheep/goats or grouse, while current TBEV-Eur strains cycle primarily between ticks and small mammals. Notably, TBEV is transmitted readily to man also via unpasteurized goat milk and cheese (Kerbo et al, 2005;Holzmann et al, 2009) in addition to tick bites.…”
Section: Rate Of Evolutionmentioning
confidence: 99%
“…These were mostly family outbreaks and included the involvement of unpasteurised goat's milk (Kriz et al, 2009). Kerbo et al (2005) reported an outbreak from Estonia in 2005 linked to raw goat's milk. An outbreak involving three cases of TBEV infection associated with the consumption of raw goat's milk were reported from Slovenia in 2012 (Hudopisk et al, 2013).…”
Section: Categorisation Of Hazards Into Main Hazards (Results Of Stepmentioning
confidence: 99%
“…To understand the described tendencies and changes in the TBE incidence during the past four-year-period as well as the fluctuation in incidence rates observed particularly during the last decade among European countries, a complex interrelation of several factors has to be considered, such as social, ecological and/or technological factors [15,[17][18][19][20][21][22][23][24]. It seems more appropriate to base a discussion of the TBE epidemiology on these factors -the importance of which can vary depending on the country -rather than on climate change alone.…”
Section: Discussionmentioning
confidence: 99%
“…An increase of TBE incidence has been observed in the risk areas (both high-and low-risk) in some of the endemic countries mentioned above, especially in the last decade [15,[17][18][19][20]. In addition, new TBE foci have appeared in Europe.…”
Section: Introductionmentioning
confidence: 95%